2019
DOI: 10.1002/lno.11364
|View full text |Cite
|
Sign up to set email alerts
|

Glomalin‐related soil protein distributions in the wetlands of the Liaohe Delta, Northeast China: Implications for carbon sequestration and mineral weathering of coastal wetlands

Abstract: Arbuscular mycorrhizal fungi (AMF) is presumably to be associated with carbon sequestration and nutrient acquisition through mineral weathering in wetland ecosystems. However, information on AMF-carbonweathering interactions is limited. Grain size, concentrations of nutrients, and the major components of 304 surface sediment samples and glomalin-related soil protein (GRSP) in 133 surface sediment samples were analyzed in various environments, including the upper delta plain wetlands (UDPW) and its adjacent sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 57 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Other authors have reported lower values of SOC, NT and glomalin in similar ecosystems. Pei et al (2019) recorded 2.30 ± 0.17 g kg − 1 glomalin in coastal wetlands inferring that glomalin content was significantly affected by the vegetation types. WenYang et al (2019), obtained 3.43 ± 0.33 g kg − 1 and 0.24 ± 0.02 g kg − 1 of SOC and NT respectively in a Chinese salt marsh mainly vegetated by Phragmites australis.…”
Section: Discussionmentioning
confidence: 93%
“…Other authors have reported lower values of SOC, NT and glomalin in similar ecosystems. Pei et al (2019) recorded 2.30 ± 0.17 g kg − 1 glomalin in coastal wetlands inferring that glomalin content was significantly affected by the vegetation types. WenYang et al (2019), obtained 3.43 ± 0.33 g kg − 1 and 0.24 ± 0.02 g kg − 1 of SOC and NT respectively in a Chinese salt marsh mainly vegetated by Phragmites australis.…”
Section: Discussionmentioning
confidence: 93%
“…For another, higher bacterial carbon metabolism activity did not lead to lower SOC in our study. This was possibly related to the decomposition ability of bacterial communities in coastal wetlands which had a lower ability to break down certain substances, such as monosaccharides, carboxylic acids, alcohols, and phenols [36][37][38]. Organic carbon is well stored in these forms.…”
Section: Possible Relationship Between Soil Carbon Content Changes An...mentioning
confidence: 99%
“…The S. alterniflora invasion led to the increase in SOC in coastal wetlands, which would lead to the increase in Proteobacteria richness and its proportion in the soil bacterial community. As for why S. alterniflora invasion areas had higher SOC when the bacterial community had higher carbon decomposition capacity, this may be related to the weak ability of soil bacteria to decompose monosaccharides, carboxylic acids, alcohols, phenols, and other substances in coastal wetlands [36][37][38]. A large amount of organic carbon may be stored in these forms.…”
Section: Possible Relationship Between Soil Carbon Content Changes An...mentioning
confidence: 99%
“…As well as vegetation species, it might also be useful to consider biogeochemical processes, which are controlled by microbial and fungal communities in wetlands. Pei et al [118] found that arbuscular mycorrhizal fungi (AMF) affected the carbon sequestration in wetlands in the northeast region of China. Remote sensing of AMF is a very new research field with some initial effort (e.g., [119]).…”
Section: Remote-sensing-based Subsurface Soc Prediction Model Framewo...mentioning
confidence: 99%